Conceptual and management perspectives of public policies in contemporaneity - Ferreira, Maria Aparecida Nascimento; Cusin, Cesar Augusto (Faculdade de Filosofia e Ciências, 2019)
Understands the conceptual aspects and management of Public Policies in contemporary society  and aims to present a theoretical framework regarding the theme and its terminologies, besides that, shows the main thinkers who contributed to the foundations of the discussions. The effectiveness of the means / instruments for the elaboration of public policies depends on the popular participation and democratic management that has a broad vision on the real necessities. It is a reflection through the current literature on the informational management of public policies at the municipal, state and federal levels in order to promote organizational performance in order to achieve success, as well as to show the circumstances of the typologies of public policies contextualized according to the purpose / function. Therefore, public policies should be thought in a rational way geared to meeting the needs of the population in order to corroborate with the quality of life, yet, the State / Government and researchers are responsible for creating and improving the laws and guidelines that govern this universe. Recebido: 16/08/2018 Aceito: 03/10/2019